Marine sponge-derived natural products: trends and opportunities for the decade of 2011-2020 - Mehbub, Mohammad Ferdous; Yang, Qi; Cheng, Ying; Franco, Christopher Milton Mathew; Zhang, Wei (Frontiers in Marine Science, 2024)
The discovery of natural products derived from marine sources has demonstrated a consistent upward trajectory for the decade of 2011-2020, holding significant promise for the development of novel drugs and many other marine bioproducts. In recent years, the spotlight has shifted away from marine sponges (Porifera) towards marine microorganisms as the primary source of discovery. Despite reports of marine sponges spanning 20 different orders and being the subject of 769 papers between 2011 and 2020, they only contributed to 19.29% of all new compounds discovered, in contrast to 51.94% by marine microorganisms and phytoplankton. 563 new compounds were reported from marine spongeassociated microbes, more than doubling the number for the previous decade (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). It heralds a positive outlook for a sustainable resource strategy as the extraction of bioactive compounds produced by pure cultures of sponge-associated microbes could overcome supply challenges that arise with isolation from host sponges for the same compound. However, the application of novel marine natural products (MNPs) remains challenging due to the limited yield of compounds from large amounts of sponges. This review covers the literature published between 2011 and 2020, focusing on MNPs isolated from marine sponges. A total of 2603 new compounds are documented, detailing their chemical classification, biological activities, source country or geographic locations, and the taxonomic information of the source organisms, including order, family, genus, and species.